2019
DOI: 10.3102/0162373719848777
|View full text |Cite
|
Sign up to set email alerts
|

Corequisite Mathematics Remediation: Results Over Time and in Different Contexts

Abstract: Traditional mathematics remediation is based on the theory that traditional mathematics remedial courses increase students’ subsequent academic performance. However, most students assigned to these courses do not pass them and thus cannot graduate. An alternative approach, corequisite remediation, assigns students instead to college-level quantitative courses with additional academic support, often aligned to a student’s major. Here, we report the longer-term results of a randomized controlled trial comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 42 publications
3
43
0
Order By: Relevance
“…The Florida College System, the California Community College and State University systems, the Texas public colleges and universities, in addition to Tennessee, have recently made optional or abolished traditional pre‐requisite remediation (Meiselman & Schudde, 2019; Mejia, 2018). Two recent randomized studies at CUNY found large statistically significant effects of assignment into developmental statistics on students’ college‐level math course completion and accumulation of credits (Logue, Watanabe‐Rose, & Douglas, 2016; Logue, Douglas, & Watanabe‐Rose, 2019). If states cannot find a model of remediation that actually increases students’ success in math, the next step would be to evaluate the consequences of eliminating remediation requirements for more students.…”
Section: Discussionmentioning
confidence: 99%
“…The Florida College System, the California Community College and State University systems, the Texas public colleges and universities, in addition to Tennessee, have recently made optional or abolished traditional pre‐requisite remediation (Meiselman & Schudde, 2019; Mejia, 2018). Two recent randomized studies at CUNY found large statistically significant effects of assignment into developmental statistics on students’ college‐level math course completion and accumulation of credits (Logue, Watanabe‐Rose, & Douglas, 2016; Logue, Douglas, & Watanabe‐Rose, 2019). If states cannot find a model of remediation that actually increases students’ success in math, the next step would be to evaluate the consequences of eliminating remediation requirements for more students.…”
Section: Discussionmentioning
confidence: 99%
“…Given the discouraging outcomes of students who begin in developmental education, a number of reforms have been devised to improve student outcomes. Reforms such as co-requisite remediation (Logue et al, 2019) and supplemental services and supports (Scrivener et al, 2015) have been found to make substantial improvements in the academic performance, persistence, and attainment of community college students. Yet these reforms often require significant investments from colleges, raising questions about their sustainability and scalability (Bettinger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of co-requisite remediation has been promoted by organizations such as Complete College America, and today approximately 20 states allow or mandate co-requisite approaches to remediation (Education Commission of the States, 2019). Although rigorous empirical evidence on this strategy is just emerging, at least one experimental study has found that being assigned to a co-requisite math course significantly improves long-term persistence and attainment when compared with traditional algebra remediation (Logue et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a policy environment where community colleges are moving away from requiring developmental education, it will be important for community colleges to provide targeted academic support for incoming women to increase their STEM participation. Co-requisite models, which can provide this type of academic support as students enroll directly in college-level courses, may be an effective strategy to meet the needs of students who would otherwise benefit from developmental coursework (Logue et al, 2019).…”
Section: Discussionmentioning
confidence: 99%